A test of the DSM‐5 severity specifier for bulimia nervosa in adolescents: Can we anticipate clinical treatment outcomes?. Issue 5 (30th January 2019) - Gorrell, Sasha; Hail, Lisa; Kinasz, Kathryn; Bruett, Lindsey; Forsberg, Sarah; Delucchi, Kevin; Lock, James; Le Grange, Daniel
Abstract: Objective: This study tested clinical utility of the DSM‐5 severity specifier for bulimia nervosa (BN) in predicting treatment response among adolescents ( N = 110) within a randomized clinical trial of two psychosocial treatments. Method: Analyses grouped individuals meeting criteria for BN diagnosis by baseline severity, per DSM‐5. Associations among baseline severity classification and BN behavior (i.e., binge eating and compensatory behavior) and eating disorder examination (EDE) Global scores at end‐of‐treatment (EOT), 6‐ and 12‐month follow‐up were examined. Results: Associations between severity categories with BN symptoms were not significant at EOT, or follow‐up. Test for linear trend in BN behavior was significant at EOT, F = 5.23, p = 0.02, without demonstrating a linear pattern. Relation between severity categories with EDE Global scores was significant at 6‐month follow‐up, F = 3.76, p = 0.01. Tests for linear trend in EDE Global scores were significant at EOT, F = 5.40, p = 0.02, and at 6 months, F = 10.73, p = 0.002, with the expected linear pattern. Discussion: Findings suggest the DSM‐5 BN severity specifier holds questionable utility in anticipating outpatient treatment response in adolescents with BN. The specifier may have improved ability to predict attitudinal rather than behavioral treatment outcomes.